(untitled) - Sergiovanni, Thomas J. (New York, NY, 2014)
The ninth edition of Supervision: A Redefinition is a research-based guide to the practice of supervision that aims to clarify the major challenges teachers and supervisors face within the policy context; focus on essential, foundational understandings that feed the integrity of teaching and supervision; and explore the complexities of the practice of supervision and teaching which supervisors must deal with. The 9th edition re-defines supervision once again in light of the complex demands being placed on principals and central office administrators, while continuing to emphasize the book’s original theme of human perspectives.
Keywords: School management and organization,Tổ chức và quản lý trường học; United States,Hoa Kỳ